Blinding trachoma in postconflict southern Sudan. - Jeremiah Ngondi; Francis Ole-Sempele; Alice Onsarigo; Ibrahim Matende; Samson Baba; Mark Reacher; Fiona Matthews; Carol Brayne; Paul Emerson (PLoS Medicine)
Background Trachoma is a leading cause of preventable blindness. Reports from eye surgery camps and anecdotal data indicated that blinding trachoma is a serious cause of visual impairment in Mankien payam (district) of southern Sudan. We conducted this study to estimate the prevalence of trachoma, estimate targets for interventions, and establish a baseline for monitoring and evaluation. Methods and findings A population-based cross-sectional survey was conducted in May 2005. A two-stage cluster random sampling with probability proportional to size was used to select the sample population. Participants were examined for trachoma by experienced graders using the World Health Organization simplified grading scheme. A total of 3,567 persons were examined (89.7% of those enumerated) of whom 2,017 were children aged less than 15 y and 1,550 were aged 15 y and above. Prevalence of signs of active trachoma in children aged 1-9 y was: trachomatous inflammation-follicular (TF) = 57.5% (95% confidence interval [CI], 54.5%-60.4%); trachomatous inflammation-intense (TI) = 39.8% (95% CI, 36.3%-43.5%); and TF and/or TI (active trachoma) = 63.3% (95% CI, 60.1%-66.4%). Prevalence of trachomatous trichiasis was 9.6% (95% CI, 8.4%-10.9%) in all ages, 2.3% (95% CI, 1.6%-3.2%) in children aged under 15 y, and 19.2% (95% CI, 17.0%-21.7%) in adults. Men were equally affected by trichiasis as women: odds ratio = 1.09 (95% CI, 0.81%-1.47%). It is estimated that there are up to 5,344 persons requiring trichiasis surgery in Mankien payam. Conclusions Trachoma is a serious public health problem in Mankien, and the high prevalence of trichiasis in children underscores the severity of blinding trachoma. There is an urgent need to implement the surgery, antibiotics, facial cleanliness, and environmental change (SAFE) strategy for trachoma control in Mankien payam, and the end of the 21-y civil war affords an opportunity to do this.